Accelaration of freeze-thaw tests by microwave heating - Türkoğlu, Amine Pınar. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1997., 1997)
The strength characteristics and hydraulic conductivity of clay liners used in waste landfills are affected by freezing and thawing cycles. To evaluate the performance of clay liners, freezing and thawing tests are needed. These tests take a long time anywhere from twenty days to twenty weeks. Microwave thawing is a new technique that can be useful to cut the testing time by half which will make these tests more practical. There are several factors that affect the strength of compacted clay among which the most important ones are method and effort of compaction, duration of one freeze and thaw cycle, number of the freeze and thaw cycles, the freezing and thawing temperatures, and when applicable the type and amount of soil additive used. In the tests, hourly and daily freezing time intervals were applied. After each freezing cycle, samples were thawed in the microwave oven at different power levels with approximately seven minutes duration. The number of cycles were five and ten. Also there was a control group with no freeze and thaw cycle. The tests were conducted on pure kaolinite, 10 per cent by weight polymer added kaolinite, pure bentonite and 40 per cent bentonite added kaolinite samples. The polymer used was waste tire fibers obtained from tire retread industry as a byproduct. The unconfined compression and direct shear tests were conducted on the compacted kaolinite and rubber added kaolinite samples before and after freeze and thaw cycles to determine the shear strength. The test results obtained by microwave oven thawing were compared with the ones obtained by conventional oven thawing. Water content determination test results have shown that microwave oven is a practical way for rapidly obtaining moisture content of soils for the specified conditions. Strength test results revealed that shear strength of the samples subjected to microwave thawing in freeze and thaw cycles was slightly higher than the shear strength of the samples subjected to conventional oven thawing, whereas the cohesion was smaller in the first case with respect to the other.
Keywords: Microwave heating.